EFFECT OF ENZYME TYPE AND HYDROLYSIS TIME ON ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF WHEY PROTEIN HYDROLYSATES - N. , Wafaa; Elbarbary, H. A.; Ibrahim, E. M. A.; Mohamed, H. A.; Jenssen, H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
There is an elevated need for novel antimicrobial preservatives in the food industry, and hydrolysis of waste products from the same sector has for decades been viewed as a potential source of these. In the current study we have purified bovine whey protein using size-exclusion chromatography (SEC), and hydrolyzed it by trypsin, pepsin, alcalase, savinase, and neutrase at different times 30, 60, 120, 240, and 300 min. The highest active time hydrolysate was subsequently fractionated by SEC, monitored for antibacterial and antioxidant activities, and characterized using UHPLC-MS/MS. Alcalase and savinase displayed higher degree of hydrolysis, higher antibacterial activity in their hydrolysates at 60 and 30 min, respectively compared to the other enzymes. The alcalase hydrolysates exhibited significantly the highest antioxidant activity rescuing 89% of the yeast cell from Hydrogen peroxide induced oxidative stress at 120 minutes. Proteomic analysis of the highly active fractions identified peptides from α-lactalbumin with structural similarity to known antioxidant peptides. Thus, our results support the using food grade enzymes like alcalase and savinase in the food industry.